Problems of optimization and the experience of making medical decisions at the admission of patients with thromboembolism of the branches of the pulmonary artery - M. A. Mel'nikov; S. E. Katorkin; M. Yu. Kushnarchuk; O. E. Kushnarchuk (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Introduction. Venous thromboembolic complications (VTE) include pulmonary embolism (PE) and deep vein thrombosis (DVT) of the lower extremities. Due to high mortality and serious complications, growing diversity and complexity in the treatment of VTE, research into the problems of optimization and experience in making medical decisions remains relevant. Aim. Analysis of existing practices of making medical decisions upon admission of patients with PE to a multidisciplinary hospital, as well as development of recommendations for their optimization. Materials and methods. An analysis of modern Russian and foreign clinical guidelines, literary scientific sources, statistical reports, and data on medical care standards for multidisciplinary medical organizations concerning the organization of diagnostics and treatment of PE was conducted. Results. The conducted analysis allowed to identify the main difficulties in making medical decisions in patients with pulmonary embolism. In the multidisciplinary Clinics of the Samara Medical University, an SOP (standard operating/working procedures) was developed and implemented, which streamlined the distribution of tasks by competence, quality assurance and logical sequence of actions in the treatment of VTE and PE. Discussion. It is essential to ensure multidisciplinary interaction between different specialists, which effectively facilitates adequate assessment of the patient's condition and planning of further treatment. Diagnosis and treatment of VTE should not be the prerogative of one narrow medical specialty. It is necessary to involve a wide range of specialists, including cardiologists, pulmonologists, cardiovascular surgeons, hematologists, neurologists, radiologists, as well as almost the entire spectrum of surgical specialties. Continuous serious attention should be paid to the education and information of medical personnel. Conclusion. Lack of experience, lack of agreed protocols for PE treatment and a well-established multidisciplinary approach to routing in a multidisciplinary hospital can lead to delays in providing effective emergency care. Experience in using modern diagnostic methods, standardized clinical routes and protocols for PE treatment contribute to improving the quality of diagnosis and therapy. However, achieving more effective results requires ongoing training and education of medical personnel, as well as the introduction of systems for regular monitoring and evaluation of treatment outcomes. The problems of optimizing medical decisions in PE require a comprehensive approach, including both organizational changes and improvement of clinical practice, which will help reduce mortality and improve treatment outcomes.